Composite sodium p-toluenesulfonate/polypyrrole/TiO2 nanotubes/Ti anode for sodium ion battery. (27th April 2017) - Liao, Qishu; Hou, Hongying; Duan, Jixiang; Liu, Song; Yao, Yuan; Dai, Zhipeng; Yu, Chengyi; Li, Dongdong
Abstract: Composite sodium p-toluenesulfonate/polypyrrole/TiO2 nanotubes/Ti was designed and synthesized for sodium ion battery anode via facile electrochemical methods. The obtained composite sodium p-toluenesulfonate/polypyrrole/TiO2 nanotubes/Ti (TsONa/PPy/TiO2 NT/Ti) electrode was investigated in terms of SEM, EDX, FTIR, galvanostatic charge/discharge and AC impedance. As expected, the composite TsONa/PPy/TiO2 NT/Ti electrode displayed higher electrochemical performances than the bare TiO2 NT/Ti electrode. For example, the reversible capacity after 50 cycles was still as high as about 200 mAh/g, higher than 170 mAh/g of TiO2 NT/Ti electrode. High Na-storage activities of both TiO2 NT and TsONa/PPy, high conductivity of TsONa-doped PPy and the synergy effect among the various components may be responsible for the improved electrochemical performances. Graphical abstract: Highlights: Composite TsONa/PPy/TiO2 NT anode was designed and synthesized for SIB. TsONa/PPy/TiO2 NT anode delivered high electrochemical performances. The underlying electrochemical mechanism was also explored and discussed. The synergy effect may be responsible for high performances.